The Effect of Classcraft Gamification on Motivation and Academic Achievement In Primary Science Education - Ummiatul Fitri; Ranti Meizatri; Hana Shilfia Iraqi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
Recent studies have highlighted persistent declines in primary students’ science motivation and engagement in the post-pandemic and digital learning era, indicating a need for pedagogical approaches that are both motivating and cognitively meaningful. However, empirical evidence on structured gamification platforms that simultaneously enhance motivation and achievement in primary science remains limited. This study examined the influence of Classcraft gamification on learning motivation and academic achievement in primary science. A quasi-experimental non-equivalent pretest–posttest control group design was employed, involving 60 fifth-grade students from an Indonesian primary school, equally assigned to an experimental group using Classcraft and a control group receiving conventional instruction. Data were collected using a Science Achievement Test (KR-20 = 0.83) and a Motivation Questionnaire (α = 0.89). Paired-sample t-tests, independent-sample t-tests, and ANCOVA were conducted to analyse group differences while controlling for pretest scores. The results demonstrated significant improvements in both achievement (from 60.13 to 85.20) and motivation (from 64.87 to 84.63) in the experimental group, with strong effect sizes (Cohen’s d > 1.70) and robust ANCOVA results (F = 60.35, p < 0.001; η² = 0.52). These findings suggest that Classcraft gamification effectively enhances motivation, collaboration, and conceptual understanding in primary science. Practically, teachers can utilize Classcraft’s role-playing and quest-based features to scaffold collaborative inquiry and sustain students’ engagement in science learning.